겨울철 염화칼슘(CaCl2) 처리에 따른 가로변 3가지 상록 관목류의 생육 및 생리반응 - 사철나무, 영산홍, 회양목을 중심으로 - 주진희; Jin Hee Ju; 박지연; Ji Yeon Park; 허혜; Hui Xu; 이은엽; Eun Yeob Lee; 현경학; Kyoung Hak Hyun; 정종석; Jong Suk Jung; et al. (한국조경학회지, 2016)
본 연구는 도심 내에서 공원 및 가로수 주변에 식재된 대표적인 세 가지 상록 관목류인 사철나무(Euonymus japonica), 영산홍(Rhododendron indicum), 회양목(Buxus koreana) 등을 중심으로 겨울철 염화칼슘(CaCl2) 처리에 따른 생육 및 생리적 반응을 살펴봄으로써, 내염성 정도와 제설제 피해지역에 대한 내성수종을 선별하기 위한 자료로 제시하고자 한다. 염화칼슘을 각각 0%(대조구), 0.5%, 1.0%, 3.0%, 5.0% 처리한 실험구에 2014년 11월에 정식한 후 이듬해 이른 봄인 2015년 3월에 수고, 엽장, 엽폭, 엽형지수, 엽수, 생체중, 건조중, 건물률, R/T율, 엽록소함량, 엽록소형광반응, 광합성률, 기공전도도, 증산율 등의 생육 및 생리적 특성을 조사하였다. 사철나무는 3.0% 이하, 영산홍과 회양목은 1.0% 이하의 처리구에서 생존이 가능하였으며, 사철나무가 영산홍과 회양목에 비해 생육적 감소율이 비교적 낮았다. 염화칼슘 처리농도가 높을수록 대조구에 비해 생리적 반응들이 감소되는 것은 동일하나, 영산홍과 회양목은 감소세가 비교적 뚜렷한 반면, 사철나무가 완만한 감소세를 보이고 있다. 특히, 처리농도가 높아짐에 따라 영산홍은 증산율을, 회양목은 광합성율과 기공전도도를 억제시키는 경향을 보였다. 이러한 결과를 통해 사철나무가 영산홍과 회양목에 비해 염해에 좀 덜 민감한 수종임을 알 수 있어 제설제 피해지역에 상록 관목류로 적용이 가능할 것으로 본다. It is important to know the sensitivity of shrubs to de-icing salt in order to set guidelines for ecological tolerance of evergreen shrubs along roads. Therefore, the aim of this study was to investigate the influence of de-icing salt, calcium chloride(CaCl2), on the growth and physiological characteristics of three evergreen shrubs, Euonymus japonica, Rhododendron indicum, and Buxus koreana. Plants were exposed to calcium chloride at different concentrations(weight percentage, 0% as control, 1.0%, 3.0%, and 5.0%) through amended soil maintained from the start of the experiment in October of 2014 until termination in March of 2015. The survival rate, plant height, leaf length, leaf width, leaf shape index, number of leaves, fresh weight, dry weight, dry matter, root/top ratio, chlorophyll contents, fluorescence, photosynthesis, stomatal conduct, and transpiration rate were recorded. Elevated calcium chloride concentrations decreased plant height, leaf length, leaf width, leaf shape index, fresh weight, dry weight, dry matter, and R/T ratio of the three shrubs. Root growth responded more sensitively than the top growth to salinity. However Euonymus japonica was more tolerant to salt stress than Rhododendron indicum and Buxus koreana. Their growths were totally inhibited by CaCl2 above 3.0% and 1.0% concentrations, respectively. Chlorophyll content, fluorescence, photosynthesis, stomatal conduct, and transpiration rate of both Rhododendron indicum and Buxus koreana were reduced sharply, while Euonymus japonica exhibited mild reductions compared to plants grown in control when increasing calcium chloride was used. Especially, the transpiration rates of Rhododendron indicum, and the photosynthesis and stomatal conduct of Buxus koreana were suppressed as the concentrations of calcium chloride increased. Therefore, Euonymus japonica should be considered as an ecologically tolerant species with proven tolerance to de-icing salt.